Datenlage im deutschen Gesundheits- und Sozialwesen - Anita B. Pfaff; Bernhard Langer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2001)
The german data on health care and social policy are very heterogeneous. Moreover they are compiled and made accessible by a large number of different institutions. The objective of the report is, as a service for students and researchers less familiar with data sources, to provide a comprehensive overview over available data in these subject areas. For this purpose a general introductory section deals with requirements of data, deficits of the existing data sources as well as recommendations for improving the situation. In a second special section information on individual statistics are presented in the form of systematic synopses. Statistics include information on the insured persons in social insurances, beneficiaries, providers of services, expenditures and revenues for benefits. The latter includes the statistics on economic aggregates as well as the distribution over socio-economic groups. Due to the extensive number of sources the presentation is confined to data compiled by public institutions (public households, ministries, social security institutions and the federal bureau of statistics) as well as two examples of a successful integration of survey data with administrative data.
urn:nbn:de:bvb:384-opus4-712555
Keywords: I18; I30; 330; public health; social policy; public finance